Digital Society: The Experience of the Philosophical Understanding of a Problem - Khazieva, Natalia O.; Khaziev, Aklim; Klyushina, Elena (Journal of History Culture and Art Research, 2018)
The focus of this study is the phenomenon of digital society which being the object of many scientific disciplines, however, still remains outside the philosophical analysis. The urgency of this analysis is dictated by the need for a holistic study of the phenomenon, its panoramic representation in the light of modern social changes. In the study, along with the "digital society", the concepts of "numerical society", "numerical world" and "digital world", "digital dimension" are analyzed, their generic relationship with the concepts "number" and "figure" is established, and also worldview grounds, features and boundaries of the use of these concepts are studied. The theoretical and methodological basis of the study is the works of ancient, medieval and modern mathematicians and philosophers on the number as an instrument of knowledge of the world and society. The author primarily uses the principle of the unity of historical and logical analysis, and relies on the principle of comparativism. The conclusion is drawn that the concept of digital society is the modern state of the information society, while the predicate "digital" reflects the final, limiting state in the development of society and the world as a whole. Thus, modern man comes to antinomy – the desire to measure the unmeasurable.